Chemical Approaches to Cell Reprogramming - Yu, Chen (Curr Opin Genet Dev, 2014)
Recent advances in cell reprogramming via employing different sets of factors, which allows generation of various cell types that are beyond the downstream developmental lineages from the starting cell type, provide significant opportunities to study fundamental biology and hold enormous promise in regenerative medicine. Small molecules have been identified to enhance and enable reprogramming by regulating various mechanisms, and provide a highly temporal and tunable approach to modulate cellular fate and functions. Here, we review the latest development in cell reprogramming from the perspective of small molecule modulation.